High-resolution P-T-Time paths across Himalayan faults exposed along the Bhagirathi transect NW India: implications for the construction of the Himalayan orogen and ongoing deformation - Catlos, Elizabeth J.; Perez, Theresa J.; Lovera, Oscar M.; Dubey, Chandra Shekhar; Schmitt, Axel Karl; Etzel, Thomas M. (Geochemistry, geophysics, geosystems, 2020)
Pressure-temperature (P-T) conditions and high-resolution paths from 11 garnet-bearing rocks collected across Himalayan fault systems exposed along the Bhagirathi River (Uttarakhand, NW India) reveal the tectonic conditions responsible for their growth. A garnet from the Tethyan metasedimentary unit has a 50.3 ± 0.6 Ma (Th-Pb, ±1σ) monazite inclusion, suggesting that ductile mid-crustal metamorphism occurred synchronously or soon after (<10 Myr) India-Asia collision, depending on timing. High-resolution garnet P-T paths from the same rock show ∼1 kbar fluctuations in P as T increases over a ∼20°C interval, consistent with a period of erosion. We report garnets from the Main Central Thrust (MCT) hanging wall that have Eocene to Miocene monazite ages, and one garnet yields paths consistent with motion along the Main Himalayan Thrust (MHT) décollement. Most high-resolution MCT footwall P-T paths fluctuate in P (±1 kbar) as T increases, consistent with imbrication and paths from equivalent structural assemblages in central Nepal. Like those rocks, MCT footwall (Lesser Himalayan Formation, LHF) monazite ages are Early Miocene (9.3 ± 0.6 Ma) to Pliocene (3.0 ± 0.2 Ma). The results demonstrate the consistency in timing and conditions across the MCT at locations ∼650 km apart. If the present-day Himalayan tectonic framework has not significantly changed since the Pliocene, the LHF duplex can be considered when attributing seismic events to particular faults. The MHT is undisputedly the significant factor in accommodating Himalayan seismic activity, but MCT footwall faults may explain some shallower hypocenters, without the need for unusual MHT geometries.
Gesehen am 10.02.2021